SISTEM RETENSI BERKAS REKAM MEDIS TERINTEGRASI: PERANCANGAN SISTEM INFORMASI BERBASIS WEB DI KLINIK PRATAMA - Hendra Rohman (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2019)
PKU Muhammadiyah Cangkringan Primary Clinic serves outpatient and inpatient services. The patient service process was still using microsoft excel, from patient registration to reporting. The problem that occurs was the accumulation of files due to not implemented the medical record file retention process, and the medical record file retention information system does not yet exist. This study aims to design a web based medical record file retention information system. The prototype design method was used as a method for developing web based information systems. The design using visual studio code editorial text and interface design with the help of a bootstrap framework, the system uses the laravel framework, and the database uses mysql. The result, a web based medical record file retention information system that can facilitate officers and doctors in viewing patient forms that have been retained, can save scans of medical record forms before they are destroyed, and can display scan results forms that have been uploaded into the information system. This information system requires patient data to see a list of visits of the last 2 years which is used to determine the medical record file that will be carried out the retention process.